Teori Hukum Progresif Dalam Melawan Penebangan Liar Di Indonesia - Gunawan, Berry (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The forestry crisis in Indonesia is multidimensional and triggers complex negative impacts primarily caused by forestry malpractice, especially illegal logging. (illegal logging). Law enforcement efforts are still weak against forest timber logging perpetrators; if there are any, they only stop at the field-level perpetrators. Therefore, the issue that arises is what comprehensive efforts can be made to prevent and eradicate illegal logging. This research attempts to identify and analyze the role of progressive law in addressing the issue of illegal logging. Basically, to stop illegal logging in Indonesia, a comprehensive approach that encompasses various aspects is needed. Progressive law applies the law by considering the normative and sociocultural aspects of society. Full appreciation and accommodation of the value of life and development within society, especially around forest areas, are very important for its operationalization. The multidisciplinary aspect of law enforcement is also very important. The orientation to combat forestry malpractice is another important component.